The status of yellow pufferfish, Xenopterus naritus (Richardson, 1848) from the Southwest coast of Sarawak, Northwestern Borneo, Malaysia - Ahmad Syafiq, Ahmad Nasir; Samsur, Mohamad; Mohammed, Mohidin (Bioflux SRL, 2017)
The yellow pufferfish, Xenopterus naritus is a commercially important target species for the artisanal fishermen in Sarawak. There is concern over its conservation and population structure. Therefore we provided a baseline data on size distribution, sex ratio, length-weight relationship and condition factor of 65 specimens of this species, landed from May 2015 to July 2014 from eight distinct locations (Kabong, Sematan, Buntal, Paloh, Sadong Jaya, Pusa, Sebangan and Spaoh) representing the Southwest coast of Sarawak waters. Specimens were obtained by hiring local fishermen to catch them and purchasing from fish markets. Generally, males were significantly smaller and lighter than females. Total length, standard length and body weight of combined sexes of X. naritus was found in the size range of 10.6–29.5 cm, 8.8–26.7 cm and 20.16–646.76 g respectively. Male to female sex ratio was 1M:2.8F. Length–weight relationships of X. naritus exhibited positive growth allometry in males but negative growth allometry in females, whereas positive growth allometry in combined sexes. Condition factor in overall specimens was 2.279±0.434 which reflects the healthiness of X. naritus and favorable environmental conditions in Sarawak waters. Findings of the present study contribute as important baseline data for future studies not only on the fisheries and stock management of X. naritus but also on conservation and aquaculture development of this commercially important species.